Neonatal Presentation of Suspected Vici Syndrome: A Case Report with Multisystem Features - Kaoutar Danaoui; Meryem Majdoul; Fatima-Ezzahra Tahiri; Hajar Akki; Kaoutar Ettouni; Mouna Zouine; Abdallah Oulmaati (Annals of African Medicine, 2026)
Abstract Vici syndrome is a rare autosomal recessive multisystem disorder caused by biallelic mutations in the EPG5 gene. It is classically characterized by agenesis of the corpus callosum, oculocutaneous hypopigmentation, combined immunodeficiency with recurrent infections, cataracts, and cardiomyopathy. We report the case of a newborn born to consanguineous parents, with a family history of a sibling death of unspecified cause, presenting with hypopigmentation, generalized hypotonia, agenesis of the corpus callosum, severe recurrent infections, developmental delay, and cleft palate. The infant also developed transient functional renal failure in the context of severe dehydration, which resolved completely after fluid resuscitation. Brain magnetic resonance imaging confirmed complete agenesis of the corpus callosum. Molecular genetic testing for suspected Vici syndrome is currently in progress. This case highlights the importance of considering Vici syndrome in neonates born to consanguineous parents presenting with agenesis of the corpus callosum, hypopigmentation, and recurrent infections. Transient renal failure may be an additional manifestation. Early recognition is essential for appropriate clinical management and genetic counseling.